High‐throughput measurement of peanut canopy height using digital surface models. Issue 1 (27th April 2020) - Sarkar, Sayantan; Cazenave, Alexandre‐Brice; Oakes, Joseph; McCall, David; Thomason, Wade; Abbot, Lynn; Balota, Maria
Abstract: Peanut ( Arachis hypogaea L.) is an important food and oilseed crop in the United States and worldwide with high net returns. However, input costs are high (US1, 970–2, 220 ha −1 ), and yield in excess of 4, 500 kg ha −1 is needed to offset the costs. Since yield is limited by biotic and abiotic stresses, newer cultivars with tolerance to these stresses are needed to optimize yield. Plant height and canopy architecture may affect crop water use and plant disease resistance. However, measuring canopy height is a time‐consuming process. Surface elevation models from red–green–blue (RGB) aerial images have been successfully developed to estimate genetic differences of plant height for tall crops like corn ( Zea mays L.) and sorghum [ Sorghum bicolor (L) Moench]; but they have not been tested for short crops like peanut with a runner growth habit and much smaller height differences among genotypes. The objective of this study was to derive canopy height of peanut from digital surface models (DSM). Images were aerially taken using a digital camera mounted on an unmanned aerial vehicle (UAV). Images were orthomosaiced to create the DSM and the digital terrain model (DTM) of the plot. Canopy height was derived by subtracting the DTM from the DSM in ArcGIS software. Results showed that the RGB derived canopy height was highly correlated to the manually measured height ( R 2 = .953). We propose the methods used here as fast and relatively easy selection tools for breeders and crop growth evaluators of peanut plant height.